Priority-Aware Downlink Frame Packing Algorithm for OFDMA-Based Mobile Wireless Systems - Bahmani, Keivan; Ince, Erhan A.; Arifler, Dogu (IEEE, 2013)
In this paper, downlink frame packing in OFDMA-based mobile wireless communication systems is addressed by extending an existing low-complexity frame packing algorithm. In particular, a realistic channel model and users with variable bit rates are used for evaluating the performance of the packing algorithms. The first extension involves allowing the unallocated bursts to be transmitted in upcoming frames. The average percentage of the unallocated bursts is improved to 0.0014% compared to 0.584% obtained with the standard eOCSA algorithm. The second extension involves assigning priorities to bursts in order to support possible quality of service requirements by users. With two different service classes, the average percentage of the unallocated bursts for the priority-aware case is 0.0048%.
21st Signal Processing and Communications Applications Conference (SIU) -- APR 24-26, 2013 -- CYPRUS
Keywords: Frame Packing; Modulation Coding Scheme; OFDMA; QoS